2010
DOI: 10.1097/aln.0b013e3181f4171b
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Small GTPase RhoA in the Development of Pulmonary Edema Induced by Pseudomonas aeruginosa  in Mice

Abstract: Background:Pseudomonas aeruginosa is an opportunistic pathogen that can cause severe pneumonia in critically ill patients. We have reported previously that P. aeruginosa exotoxins S and T mediate in vitro the increase in protein permeability across lung endothelial cell monolayers via a RhoA-dependent mechanism. However, whether inhibition of RhoA would significantly attenuate P. aeruginosa-mediated lung injury in mice is unknown. Methods: P. aeruginosa-induced paracellular protein permeability was measured ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Our laboratory demonstrated that ExoS and ExoT, two cytotoxins from the Type III secretion system, are responsible for the P. aeruginosa-mediated increase in protein permeability across lung endothelial cell monolayers via the inhibition of Rac1, combined with the activation of RhoA (13). In a subsequent in vivo study, we found that the inhibition of RhoA attenuated the increase in lung endothelial and alveolar epithelial permeability to protein and the development of pulmonary edema, and further, that this restored positive alveolar fluid clearance in a murine model of P. aeruginosa pneumonia (14). Thus, we hypothesized that the mediators decreasing the activity of RhoA in the lung cells constituting the alveolar-capillary barrier may attenuate the lung damage caused by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our laboratory demonstrated that ExoS and ExoT, two cytotoxins from the Type III secretion system, are responsible for the P. aeruginosa-mediated increase in protein permeability across lung endothelial cell monolayers via the inhibition of Rac1, combined with the activation of RhoA (13). In a subsequent in vivo study, we found that the inhibition of RhoA attenuated the increase in lung endothelial and alveolar epithelial permeability to protein and the development of pulmonary edema, and further, that this restored positive alveolar fluid clearance in a murine model of P. aeruginosa pneumonia (14). Thus, we hypothesized that the mediators decreasing the activity of RhoA in the lung cells constituting the alveolar-capillary barrier may attenuate the lung damage caused by P. aeruginosa.…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, ExoS and ExoT, two cytotoxins from the Type III secretion system, are responsible for the P. aeruginosa-mediated increase in protein permeability across lung endothelial cell monolayers via an inhibition of Rac1 and an activation of RhoA (13). In an in vivo study, we found that the inhibition of RhoA attenuates the increase in lung endothelial and alveolar epithelial permeability to protein, the development of pulmonary edema, and the inhibition of alveolar fluid clearance in a murine model of P. aeruginosa pneumonia (14). aPC favorably elevates the ratio of Rac1/RhoA activity in the lung endothelium, apparently by activating the S1P pathway through EPCR/PAR-1-dependent mechanisms, and indirectly by preventing the formation of thrombin and its detrimental effects on the barrier properties of the lung endothelium and alveolar epithelium (4).…”
Section: Clinical Relevancementioning
confidence: 86%
See 3 more Smart Citations